2019 State of Climate Services: Agriculture and Food Security - Dobardzic, Saliha; Dengel, Cristina G.; Gomes, Alyssa Maria; Hansen, James; Bernardi, Michele; Fujisawa, Mariko; Heureux, Ana M.; Kanamaru, Hideki; Neretin, Lev; Rojas, Oscar; Intsiful, Joseph; Barnwal, Aloke; et al. (World Meteorological Organization, 2019)
In 2018, the Conference of the Parties serving as the meeting of the Parties to the Paris Agreement at the 24th Conference of the Parties to the United Nations Framework Convention on Climate Change (UNFCCC) called on the World Meteorological Organization (WMO) through its Global Framework for Climate Services (GFCS) to regularly report on the state of climate services with a view to “facilitating the development and application of methodologies for assessing adaptation needs” (Decision 11/CMA.1). This inaugural 2019 State of Climate Services Report focuses on agriculture and food security. It reviews countries’ priorities on climate services for adaptation, noting that agriculture is one of the highest, and identifies priority capacity needs. It examines capacity gaps across six components of the climate services value chain including: governance, basic systems, user interface, capacity development, provision and application of climate services, and monitoring and evaluation. The report provides case studies, examples and explanations as to the role of climate information and services to support agriculture in the face of climate variability and change, assesses gaps and makes recommendations. This analysis helps highlight both challenges and opportunities for climate service efforts aimed at promoting climate resilient development and adaptation action.